Concentration Fluctuation in Long Wavelength Limit in Liquid Magnesium Alloy - Adhikari, D; Singh, B. P.; Jha, I. S. (Himalayan Physics, 2011)
The microscopic structure of MgSn liquid alloy at 1073K has been studied by using regular associated solution model. For this we have calculated the concentration fluctuation in long wave length limit [SCC(0)] and chemical short range order parameter (α1) of liquid MgSn alloy at 1073 K. Keywords: Binary Alloy; Complex; Chemical order; Microscopic Function The Himalayan Physics Vol.2, No.2, May, 2011 Page: 47-49 Uploaded Date: 1 August, 2011